Distal ash fall from the mid-Holocene eruption of Mount Hudson (H2) discovered in the Falkland Islands: New possibilities for Southern Hemisphere archive synchronisation. (15th August 2021) - Panaretos, Panayiotis; Albert, Paul G.; Thomas, Zoë A.; Turney, Chris S.M.; Stern, Charles R.; Jones, Gwydion; Williams, Alan N.; Smith, Victoria C.; Hogg, Alan G.; Manning, Christina J.
Abstract: Cryptotephra deposits (microscopic volcanic ash) are important geochronological tools that can be used to synchronize records of past environmental change. Here we report a distal cryptotephra from a Holocene peat sequence (Canopus Hill) in the Falkland Islands, in the South Atlantic. Using geochemical analysis (major- and trace-element) of individual volcanic glass shards, we provide a robust correlation between this cryptotephra and the large mid-Holocene explosive eruption of Mt. Hudson in Patagonia, Chile (H2; ∼3.9 ka cal BP). The occurrence of H2 as a cryptotephra in the Falkland Islands significantly increases the known distribution of this marker horizon to more than 1200 km from the volcano, a threefold increase of its previous known extent. A high-resolution radiocarbon chronology, based on terrestrial plant macrofossils, dates the H2 tephra to 4265 ± 65 cal yr BP, suggesting that the eruption may have occurred slightly earlier than previously reported. The refined age and new geochemical reference dataset will facilitate the identification of the H2 tephra in other distal locations. The high concentration of glass shards in our peat sequence indicates that the H2 tephra may extend well beyond the Falkland Islands and we recommend future studies search for its presence across the sub-Antarctic islands and Antarctic Peninsula as a potentially useful chronological marker. Highlights: Microscopic volcanic ash layer discovered in Falkland Islands Holocene peat bog. Layer is chemically correlated to the mid-Holocene eruption of Mount Hudson (H2) in Patagonia. This identification significantly extends the previously known distribution of Mt Hudson products. Major and trace elemental reference data available to facilitate the identification of H2 tephra. H2 tephra may be more widespread than yet identified and is an important isochron.